An association rule-based recommendation engine for online dating sites - Özseyhan, Yağız Civan. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
In this study, the database of a Turkish online dating site is analyzed to reveal patterns in the personal features of matching couples. By using a functionality of data mining, the Association Rule mining, a set of rules is extracted from the available messaging and user data. The rules are used for the development of a recommendation engine which is capable to give list of best potential matches to the site user. The performance of the recommendation engine is tested with statistical tools to find whether the increase in the quality of results is significant.
Keywords: Online dating.; Data mining.